Study of The Relationship Between Telecommunication Infrastructure and Gross Domestic Product In Indonesia - Gregorius Numan Sungkalang; Josephine Wuri; Laurentius Bambang Harnoto; Yuliana Rini Hardanti (Publikasi Indonesia, 2025)
Telecommunication infrastructure has a crucial role in driving the growth of a country's Gross Domestic Product (GDP). Telecommunications infrastructure can improve operational efficiency in various sectors of the economy, such as trade and services, which utilize information and communication technologies. This study aims to analyze the relationship between telecommunication infrastructure and Gross Domestic Product (GDP) in Indonesia. The data used in this study are annual secondary data derived from the World Development Indicators for the period 2000 to 2023. The analysis tool used is multiple linear regression to analyze the relationship between telecommunication infrastructure and Gross Domestic Product in Indonesia. The results of the study show that the simultaneous influence of the internet and telephone telecommunication infrastructure on Gross Domestic Product is positive and significant. The test results also show that internet telecommunication infrastructure has a positive and significant effect on Gross Domestic Product, while telephone telecommunication infrastructure has a negative and significant effect. This research provides important insights for policymakers in formulating telecommunication infrastructure development strategies to increase Gross Domestic Product in Indonesia.